Implementasi Hazops untuk Mengidentifikasi Potensi Bahaya K3 pada Area Instalasi Pengolahan Air Limbah (IPAL) - Bastuti, Sofian; Alfatiyah, Rini (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
In the modern industrial era, waste management becomes a crucial aspect that not only impacts the environment but also occupational safety and health (OSH) in the workplace. The Wastewater Treatment Plant (WWTP) area represents a critical zone that requires special attention regarding risk management and the potential hazards that may arise. The potential OSH hazards in the WWTP area include electric shock, poisoning, skin irritation, eye irritation, respiratory distress, and slipping. This study aims to explore the application of HAZOP (Hazard and Operability Study) as a tool for identifying, assessing, and managing risks in the WWTP area. The implementation of HAZOP is considered an effective strategy for reducing the potential OSH hazards in the WWTP area. HAZOP, which is one of the most widely recognized risk and safety analysis techniques, allows for the systematic identification of potential hazards as well as operational deviations that may occur in the wastewater treatment process. The findings of this study indicate that the level of OSH risk in the WWTP area is high at 55%, medium risk at 20%, and low risk at 25%. Keywords: HAZOP, OHS Hazard Potential, WWTP